Contribution of Co-operatives on Women Empowerment - Pokharel, Ram Raj (Patan Prospective Journal, 2023)
Abstract Cooperatives provide financial and social intermediaries, particularly for women and the underprivileged. Microcredit, micro savings, micro insurance, and micro remittance are among the financial services offered by cooperatives. The simple services of cooperatives attracted backward women, which may have pushed women in that direction. The empowerment of women has been identified by the researcher as the new horizon in this article. When women are empowered, they are independent, enjoy unrestricted movement, and can participate freely in the sectors and fields of their choice. When women achieve economic, social and political strength, the concept of empowerment acquires its full meaning. In this view, the investigation and identification of the role cooperatives have played in raising social and economic status are the main objectives of the study. In order to ensure the study's validity from a review of the literature, data from interviews with members of the Opi Saving and Credit Co-operative in Kirtipur Municipality Ward No. 6 in the Kathmandu District were used as a sample. There are 136 respondents in the sample. According to the study's findings, the co-operative's benefits to women have improved their incomes and raised their standard of life. As a result of their participation, communication, fund management discussions, cooperative power, and accountability, the study's member co-operative women are growing more physically and cognitively engaged.